Investigation of interfacial mechanical properties of graphene-polymer nanocomposites. Issue 14 (21st September 2016) - Liu, Feng; Hu, Ning; Han, Meng; Atobe, Satoshi; Ning, Huiming; Liu, Yaolu; Wu, Liangke
Abstract: A series of graphene (GR) pull-out simulations based on molecular dynamics (MD) were carried out to investigate the interfacial mechanical properties between GR and a polymer matrix (polyethylene: PE). The effects of pull-out velocity, number of vacancy defect in GR and temperature on the interfacial mechanical properties of a GR/PE nanocomposite system were explored. The obtained results showed that the pull-out velocity and the temperature have significant influences on the interfacial mechanical properties for a perfect GR. Moderate vacancy defects in GR can effectively enhance the interfacial mechanical properties in GR-based polymer nanocomposites.